Safety and digital economy in the global south: an educator’s approach (2024)
The rapid growth of the digital economy has created various opportunities for individuals, organisations and communities particularly in the Global South. High rates of poverty and wealth inequality plague many of the Global South nations such as China, India, Indonesia, Brazil, Pakistan, among others which has resulted in notable differences in the digital divide and restricted access to education. Education systems in the Global South often face challenges such as inadequate infrastructure, insufficient funding, and a shortage of qualified teachers. The digital economy’s disruptive effect can also be seen in a variety of sectors, including health, family life, financial services and communication networks. These problems require safeguarding individuals’ safety and security in the ever-changing contexts. This paper uses systematic literature and critical analysis to investigate the main significant benefits of an internet-based economy with improved access to information and markets, job prospects, and economic growth. It will then introduce the notion of safety education in a digital economy and its role in equipping individuals to traverse the digital landscape. Safety education can help to reduce the risks posed by digital economy.